PENGARUH PARTISIPASI ANGGOTA TERHADAP KINERJA PENGURUS KUD KAMPAR KECAMATAN KAMPA KABUPATEN KAMPAR - Desriyanti, Desriyanti; Makhdalena, Makhdalena; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine and analyze the effect of member participation on the cooperative management's performance. The population in this study were members of KUD Kampar, Kampa district, Kampar district. Numbering 725 people, the total sample of 88 people was taken using the formula (Slovin). The sampling technique used wastechnique proportional random sampling. Data collection techniques using a questionnaire. The data analysis technique used is simple linear regression analysis. The results of this study indicate that member participation has a positive and significant effect on the performance of the KUD Kampar management, Kampa District, Kampar Regency.Key Words: Member Participation, Management Performance